Multi-spectrum robotic cardiac surgery: Early outcomesCentral MessagePerspective - Husam H. Balkhy, MD; Sarah Nisivaco, BS; Gianluca Torregrossa, MD; Hiroto Kitahara, MD; Brooke Patel, APN; Kaitlin Grady, PA-C; Charocka Coleman, APN (JTCVS Techniques)
Objective: The robotic cardiac surgery program at our current institution began in 2013 with an experienced and dedicated team. This review analyzes early outcomes in the first 1103 patients. Methods: We reviewed all robotic procedures between July 2013 and February 2021. Primary outcomes were mortality and perioperative morbidity. Our robotic approach is totally endoscopic for all cases: off-pump for coronary and epicardial procedures, and on-pump with the endoballoon for mitral valve and other intracardiac procedures. Results: There were 1103 robotic-assisted cardiac surgeries over 7 years. A total of 585 (53%) were off-pump totally endoscopic coronary artery bypasses, 399 (36%) intracardiac cases (including isolated and concomitant mitral valve procedures, isolated tricuspid valve repair, CryoMaze, atrial or ventricular septal defect repair, benign cardiac tumor, septal myectomy, partial anomalous pulmonary venous drainage, and aortic valve replacement); 80 (7%) epicardial electrophysiology-related procedures (epicardial atrial fibrillation ablation, left atrial appendage ligation, lead placement, and ventricular tachycardia ablation); and 39 (4%) other epicardial procedures (pericardiectomy, unroofing myocardial bridge). Mortality was 1.2% (observed/expected ratio, 0.7). In the totally endoscopic coronary artery bypass and intracardiac groups, mortality was 1.0% (observed/expected, 0.6) and 1.5% (observed/expected, 0.87), respectively. There were 8 conversions to sternotomy (0.7%) and 24 (2.2%) take-backs for bleeding. Mean hospital and intensive care unit lengths of stay were 2.74 ± 1.26 days and 1.28 ± 0.57 days, respectively. Conclusions: This experience demonstrates that a robotic endoscopic approach can safely be used in a multitude of cardiac surgical procedures both on- and off-pump with excellent early outcomes. An experienced surgeon and team are necessary. Longer-term follow-up is warranted.